Evaluation Problem versus Selection Problem in Organizational Structures - Stefano Ficco; Vladimir Karamychev (Tinbergen Institute, 2005)
We consider a hierarchical organization with two fully rational agents. The goal of the organization is that of selecting the best alternative out of several available, and agents are heterogenous in the accuracy with which they screen the alternatives. We show that, if internal communications between agents is not possible, the ordering of agents affects the performance of the organization. More specifically, we find that the expected payoff of the organization improves when the more accurate agent screens first. Finally, we note that such optimal ordering makes the hierarchy formally identical to one in which the internal communication flow is perfect.
Keywords: D23; D70; D81; 330; Organizations; Imperfect Communication; Selection; Organisationsstruktur; Unternehmensorganisation; Interne Kommunikation; Theorie